Fotografia digital no diagnóstico e documentação de trincas e cor dentária - Swarowsky, Luciana Abitante (2022)
The potential of digital photography in Dentistry has been scientifically proven throughout its existence. The development of macro photography allowed dental professionals to accurately reproduce and communicate the most diverse clinical aspects. In the present work, two laboratory studies are presented about the use of digital photography as a means of diagnosis and documentation of different dental specificities. The first study, "Diagnosis and documentation of cracked tooth syndrome using different photographic techniques" evaluated the detection and documentation of tooth cracks through photographic images captured by seven photographic techniques. For this, 135 naturally cracked teeth were photographed in a standardized way by a digital camera (Canon EOS Rebel T6) equipped with a 100-mm macro lens associated with transillumination, circular flash and twin flash. Likewise, a smartphone (Apple iPhone 6) equipped with macro lens and external light, macro lens and transillumination, external light and transillumination was used. The study showed that the detection and documentation of crack lines differ according to the photographic technique used, and the visualization of cracks may be influenced not only by the light applied during the photographic process, but also by the type of magnification. The detection and documentation of dental cracks improved significantly when the image capture was associated with transillumination, regardless of the camera used. The second study, "Influence of image file and white balance on photographic color assessment", was developed in view of the need to understand the influence of the photographic file format and the white balance on the process of selecting and documenting tooth color. For this, photographs of 10 dental shade guides were captured in a standardized way, stored in RAW, JPEG and TIFF formats, and evaluated in a specific image program, before and after the white balance adjustment. The main findings showed that the image file formats tested documented different tooth color guides. Both the JPEG and TIFF image files, when originated from the RAW format with adjusted white balance, showed excellent ability to represent the color of the dental shade guide when visual perceptibility and acceptability thresholds were considered. In addition, the findings also showed that the use of the gray card of known color coordinates provided greater standardization of the recorded color, regardless of the image file format and/or the shade tab color.